2006
DOI: 10.1002/app.25268
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of uncrosslinked and chemically crosslinked polyethylene/ethylene vinyl acetate copolymer blends

Abstract: Uncrosslinked and chemically crosslinked binary blends of low-and high-density polyethylene (PE), with ethylene vinyl acetate copolymer (EVA), were prepared by a melt-mixing process using 0-3 wt % tert-butyl cumyl peroxide (BCUP). The uncrosslinked blends revealed two distinct unchanged melting peaks corresponding to the individual components of the blends, but with a reduced overall degree of crystallinity. The crosslinking further reduced crystallinity, but enhanced compatibility between EVA and polyethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 20 publications
7
29
0
Order By: Relevance
“…In order to improve the rubbery properties of EVA, the crosslinked form of this thermoplastic has also been applied in industries . However, many published researches have evaluated the crystallization behavior of EVA with or without crosslinking agents . Khonakdar et al have studied the melting and crystallization characterizations of EVA in the range of −75°C to 175°C and showed that the weight fraction of crystallinity reduces as a result of polymer chain crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the rubbery properties of EVA, the crosslinked form of this thermoplastic has also been applied in industries . However, many published researches have evaluated the crystallization behavior of EVA with or without crosslinking agents . Khonakdar et al have studied the melting and crystallization characterizations of EVA in the range of −75°C to 175°C and showed that the weight fraction of crystallinity reduces as a result of polymer chain crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…However, the PE/DCP showed improved injection moldability under 135-145 ºC and 50-60MPa as shown in Fig.2 (d) to (f). Introduction of DCP into PE increases the melt viscosity and shear modulus of PE [3]. Therefore, the recycled PE materials with DCP showed poor injection moldability with DCP introduction increasing when the injection was conducted at 175-230 °C and 35-40 MPa, while improved injection moldability under 135-145ºC and 50-60MPa.…”
Section: Methodsmentioning
confidence: 99%
“…And it has been demonstrated that ethylene-vinyl acetate copolymer (EVA) and Dicumyl peroxide (DCP) were effective modifiers. It is reported that introduction of EVA can increase the elongation at the break and tensile strength for the LDPE/EVA blends, while a reverse trend for the HDPE/EVA [2,3]. And Introduction of 2 wt.% dicumyl peroxide (DCP) can simultaneously improve the tensile strength and elongation at break [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it can increase the tensile strength of polymers and thus, at a reasonable yield of crosslinking, improve their mechanical properties. 21 The crosslinking process involves the formation of chemical bonds (crosslinks) between adjacent molecular chains to form a threedimensional network. There exist several methods to produce crosslinked polymers, such as chemical methods, using mainly peroxides 22 or silanes, 23,24 and high-energy irradiation (electronic beam) techniques.…”
Section: Introductionmentioning
confidence: 99%